Sistem Informasi Manajemen Distribusi Pupuk Bersubsidi Berbasis Chatbot - Abu Sofyan, Mukhmat; Sifaunajah, Agus; Khafidhoh, Nur (SAINTEKBU, 2021)
Management Information System is a system used to organize online sales transactions. This study developed a management information system for Ud Anggi Jaya where there were several problems such as price, lack of transparency in the process of ordering fertilizers, errors in recording orders, and it took a little longer in making reports. For that, as part of an innovation that supports customer service, the technology that will be used is a chatbot. The chatbot function is here to help customers handle incoming messages via various communication channels. The chatbot ensures that all messages from customers can be handled quickly. About a business and product in this business, the author uses the waterfall research methodology. This methodology is composed of 4 stages, 1) System Analysis Stage, 2) Design Stage, 3) Coding Stage, 4) Testing stage. This system was developed in the programming language PHP and MySql as a database management system, in this system there are product data, sales data, distributor data and sales reports, so that the subsidized Fertilizer Management Information System can help simplify the fertilizer transaction process, and as a promotion media.